2022
DOI: 10.17503/agrivita.v44i1.3079
|View full text |Cite
|
Sign up to set email alerts
|

The Yield Stability and Adaptability of Bambara Groundnut at Three Locations

Abstract: Varieties with high yield stability are required to increase the yield. This study examines the strength and adaptability of seven Bambara groundnut lines in three areas. The seven lines used are CCC 1.6, PWBG 6, PWBG 521, SS 342, SS 242, BBL 11, and TVSU 86 as checks. The research sites are Brawijaya University Experimental Station, Farmer field in Madiun and Indonesia Legumes, and Tuber Crop Research Institute (ILETRI) Research Station. Research is conducted from February to October 2020. The study used a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 16 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…In terms of selection, these suggested that trait improvement will only be effective after selection in the advanced generations and that the selection of these traits in subsequent early generations could lead to unpredictable genetic gains. The nonadditive gene action found in this study were in concurrence with Shiferaw (2022), who reported that grain yield was controlled by non-additive gene action. Heritability is a useful measure of the proportion of variance observed among genotypes due to genetic differences and is expressed in a broad and narrow sense genetic control of traits (Oppong-Sekyere et al…”
Section: Discussionsupporting
confidence: 91%
“…In terms of selection, these suggested that trait improvement will only be effective after selection in the advanced generations and that the selection of these traits in subsequent early generations could lead to unpredictable genetic gains. The nonadditive gene action found in this study were in concurrence with Shiferaw (2022), who reported that grain yield was controlled by non-additive gene action. Heritability is a useful measure of the proportion of variance observed among genotypes due to genetic differences and is expressed in a broad and narrow sense genetic control of traits (Oppong-Sekyere et al…”
Section: Discussionsupporting
confidence: 91%
“…This result is similar to those reported by [18] which states that there was no significant variation in studied parameters such as mean plant height, number of leaves, number of branches and canopy spread between two Bambara ground varieties used from their study. Another study report by [19] on yield adaptability and stability of selected Bambara groundnut revealed that parameters such as mean canopy spread, plant height and number of pods in Bambara groundnut do not show any significant difference, however, little differences were observed among different varieties. Results on plant canopy spread indicated diverse performance among the landraces used.…”
Section: Resultsmentioning
confidence: 93%
“…Landraces unfold their potential when they are cultivated per se in the regions where they have been adapted, and despite their low productivity in ex situ cultivation, they should be further evaluated on-farm in each one’s region of origin. Therefore, the performance, including both productivity and stability of the examined landraces of the present experiment, should also be assessed in their region of origin as well as in other soil and climatic environments [ 49 , 87 , 88 , 89 , 90 ], as different cowpea landraces were found to be better adapted to diverse environments [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, landraces consist of genetic material with intermediate yield, production efficiency, and yield stability when they are cultivated in low-input cropping systems [ 43 , 44 ] and are easier to access and use in breeding for desirable traits compared to crop wild relatives. Therefore, they are important in terms of stable yield production [ 45 , 46 ] and of improving resistance to various abiotic stresses [ 47 , 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%